Impact of Conflict on Adolescent Girls in South Sudan - Pape, Utz; Phipps, Verena (World Bank, Washington, DC, 2018)
Violent conflict and instability affect men and women in heterogeneous ways, including differentiated impacts on economic, social, physical, and mental well-being. This study assesses the impact of the post-2013 conflict in South Sudan on adolescent girls and young women. The analysis uses data from the Adolescent Girls Initiative endline survey and the Armed Conflict Location & Event Data to measure conflict exposure using constructed cluster-level, self-reported, and external conflict exposure variables. The impact of conflict exposure is then estimated on a set of socioeconomic outcomes of adolescent girls by comparing exposed and non-exposed clusters before and after the conflict. The results suggest that girls from clusters more affected by the conflict had statistically different outcomes compared with girls from less affected clusters. Specifically, there is strong evidence that the conflict negatively affected outcomes related to income opportunities, aspirations, marriage, and household characteristics, but increased self-reported empowerment and entrepreneurial potential scores. The results indicate that impacts on labor supply, personal motivation, household conditions, and other forms of victimization are important channels through which conflict negatively impacts adolescent girls.